2019
DOI: 10.1103/physrevd.100.023012
|View full text |Cite
|
Sign up to set email alerts
|

Future prospects for constraining nuclear matter parameters with gravitational waves

Abstract: 1 Piecewise polytropic constructions [19-21] and spectral EoSs [8, 22-25] similarly parameterize nuclear matter EoSs in a modelindependent way. See also [12, 26] for related works on piecewise unified EoSs. arXiv:1906.05978v2 [gr-qc]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…More specifically, (1) and (2) were from Malik et al [64] and (3), (4), and (5) from Biswas et al [65]. The rest were from (6) Zimmerman et al [88], (7) Tsang et al [66], (8) Xie and Li [67], (9) Baillot d'Etivaux et al [68], (10) Malik et al [69], (11) Lim and Holt [71], (12) Chamel et al [75], (13) Raithel and Özel [79], (14) Carson et al [89], (15) Yue et al [80], and (16) Essick et al [81]. The average of these 16 new analyses was about K sym ≈ −107 ± 88 MeV at a 68% confidence level.…”
Section: Updated Systematics Of Symmetry Energy Parameters At ρ 0 After Incorporating the Results Of Recent Analyses Of Neutron Star Obsementioning
confidence: 99%
“…More specifically, (1) and (2) were from Malik et al [64] and (3), (4), and (5) from Biswas et al [65]. The rest were from (6) Zimmerman et al [88], (7) Tsang et al [66], (8) Xie and Li [67], (9) Baillot d'Etivaux et al [68], (10) Malik et al [69], (11) Lim and Holt [71], (12) Chamel et al [75], (13) Raithel and Özel [79], (14) Carson et al [89], (15) Yue et al [80], and (16) Essick et al [81]. The average of these 16 new analyses was about K sym ≈ −107 ± 88 MeV at a 68% confidence level.…”
Section: Updated Systematics Of Symmetry Energy Parameters At ρ 0 After Incorporating the Results Of Recent Analyses Of Neutron Star Obsementioning
confidence: 99%
“…This observation clearly reject the NL3 and IU-FSU phenomenological model in determining the NM parameters for astrophysical observations and hints for G3 EoS, best suited for the study of astrophysical phenomena. Studies show that there is a strong correlation between K sym,0 , tidal deformability and R 1.4 (radius of NS with mass 1.4 M ) [63][64][65]. By obligating K sym,0 in the befitting range we can measure tidal deformability theoretically, which is quite a complicated quantity to measure independently, precisely upto a certain level of accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have empirically identified correlations between various combinations of parameters that characterize the symmetry energy and its density dependence with the neutron star radius and tidal parameters [246,[266][267][268][269] or terrestrial experimental results [239,[270][271][272], as they all are linked to the low-density behavior of the equation of state around (twice) saturation. The tidal constraints from GW170817, and more recently radius constraints from NICER have been used to examine implications for the symmetry energy [273][274][275][276][277][278][279][280][281][282] as well as potential systematics in the mapping [283].…”
Section: Microscopic Propertiesmentioning
confidence: 99%